2020
DOI: 10.1038/s41598-020-71877-z
|View full text |Cite
|
Sign up to set email alerts
|

Eye lymphatic defects induced by bone morphogenetic protein 9 deficiency have no functional consequences on intraocular pressure

Abstract: Aqueous humor drainage is essential for the regulation of intraocular pressure (IOP), a major risk factor for glaucoma. The Schlemm’s canal and the non-conventional uveoscleral pathway are known to drain aqueous humor from the eye anterior chamber. It has recently been reported that lymphatic vessels are involved in this process, and that the Schlemm’s canal responds to some lymphatic regulators. We have previously shown a critical role for bone morphogenetic protein 9 (BMP9) in lymphatic vessel maturation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…A denser distribution of conjunctival lymphatic vessels at the nasal side of the eyeball was previously reported in a model of induced corneal lymphangiogenesis [28]. The observation of a temporal-nasal polarized distribution has recently been confirmed by innovative techniques, such as LSFM, combined or not with optical clearing of the intact pigmented mouse eyeball, that have allowed the 3D visualization of the lymphatic topography of the whole mouse ocular surface lymphatic network [27,29] (Figure 2).…”
Section: Anatomy Of the Eye Lymphatic Vascular Systemsupporting
confidence: 62%
See 4 more Smart Citations
“…A denser distribution of conjunctival lymphatic vessels at the nasal side of the eyeball was previously reported in a model of induced corneal lymphangiogenesis [28]. The observation of a temporal-nasal polarized distribution has recently been confirmed by innovative techniques, such as LSFM, combined or not with optical clearing of the intact pigmented mouse eyeball, that have allowed the 3D visualization of the lymphatic topography of the whole mouse ocular surface lymphatic network [27,29] (Figure 2).…”
Section: Anatomy Of the Eye Lymphatic Vascular Systemsupporting
confidence: 62%
“…In these studies, the bulbar conjunctiva covering the bulbar sclera, was observed to display a rich network of lymphatic vessels composed of initial lymphatics that drains into LYVE-1-positive precollectors containing valves [27]. As illustrated on the scheme in Figure 3, the ocular surface lymphatics were observed to converge at the nasal canthus by large lymphatic trunks displaying lower LYVE-1 expression and draining either the dorsal or the ventral side of the eyeball [27].…”
Section: Anatomy Of the Eye Lymphatic Vascular Systemmentioning
confidence: 88%
See 3 more Smart Citations